# Solve the following: x + 9y = -26 -2x + 4y = -36

### 2 Answers | Add Yours

The system of equations

x + 9y = -26 ...(1)

-2x + 4y = -36 ...(2)

has to be solved.

x + 9y = -26

=> x = -9y - 26

substitute in (2)

=> -2(-9y - 26) + 4y = -36

=> 18y + 52 + 4y = -36

=> -22y = -88

=> y = 4

x = 36 - 26 = 10

**The solution of the set of equations is x = 10 and y = 4**

1---- x + 9y = -26

2 --- -2x + 4y = -36

1----

x + 9y = -26

x = -9y - 26

puting value in 2

-2(-9y -26) +4y = -36

18y + 52 + 4y = -36

22y = -36 -52

22y = -88

y = -4

put the value y= -4 in 1

x + 9y = -26

x + 9(-4) = -26

x - 36 = -26

x = 10

SS= (x,y) = ( 10, -4)